PELAKSANAAN TUGAS STEWARD DI BATIQA HOTEL PEKANBARU - Wina Silvia Agustin; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is entitled Implementation of Steward Tasks at Batiqa Hotel Pekanbaru. This study aims to find out how the implementation of steward duties at Batiqa Hotel Pekanbaru, besides that what are the obstacles in the implementation of steward duties, and what are the solutions to face obstacles when implementing stewards at Batiqa Hotel Pekanbaru. This research is also a qualitative research method with a descriptive approach used in this study, with data collection techniques used in this study in the form of interviews, document studies, observation. Key informants involved in this research are Chief Steward, Silvermen, and Night Steward. Based on the results of the research, the Implementation of Steward Tasks at Batiqa Hotel Pekanbaru has been going well and according to the Standard Operational Procedure (SOP). But of course there must be obstacles faced by the Steward during the implementation of steward duties at the Batiqa Hotel Pekanbaru such as during inventory, when handling wet waste or handling dry waste, when maintaining the cleanliness of the kitchen area or maintaining cleanliness around the kitchen, when handling utensils, when providing tools. -tools, when cleaning tools, when distributing tools, when caring for tools, when storing tools but the obstacles faced by the steward can be overcome with the best solutions from the steward. Key words: steward, handling and prepare an equipment.